“Last Night, I Prayed to Matthew”: Matthew Shepard, Homosexuality, and Popular Martyrdom in Contemporary America - Hoffman, Scott W. (Religion and American culture, 2011)
In October 1998, Matthew Shepard, a young gay student at the University of Wyoming, was brutally murdered. Upon hearing the news, many Americans described him as a victim of a hate crime. Others, however, proclaimed Shepard a gay martyr. This declaration was not simply political rhetoric. Despite long-standing conservative religious opposition to homosexuality, they believed that Shepard had been granted salvation and a place among the saints in heaven. This article addresses the questions, “How and why was Matthew Shepard declared a popular martyr?” More specifically, how does this popular martyrdom relate to contemporary debates surrounding civil rights for gays and lesbians in America? As part of a series of social movements that followed the Second World War, sexual minorities have struggled to claim legitimate space in American society, leaving dramatic social changes in their wake. Noting this, while contrasting the news media’s construction of Shepard with the simultaneous popular discussion on the Internet, this article argues that a long tradition of popular martyr-making came together with social and political circumstances at a certain historical moment to transform the obscure victim of a hate crime into a popular martyr residing in heaven. That is, although the news media constructed Shepard as simply the affable young victim of a fatal hate crime, these contingencies allowed many Americans to reconstruct Shepard as a popular martyr. They expressed this belief in political, cultural, and social action. In time, Shepard's popular martyrdom helped further a growing acceptance of gays and lesbians into America's mainstream.